An Approach to Assessing Farm-Scale Adaptation to Climate Change: The Case Study of Prespa Park - GRAZHDANI, Dorina (Journal of Environmental Management and Tourism; Vol 15 No 2 (2024): JEMT, Volume XV, Issue 2(74), Summer 2024, 2024)
Developing appropriate adaptation practices and coping mechanisms for climate change and evaluating the variables affecting households’ choices are critical for ensuring sustainable agricultural production. In addressing the above issues, this paper presents the results of a multi-method approach at the farm level conducted in the case study of Prespa Park. The data collected by a participatory process were analyzed using descriptive statistics, the 5-point Likert scale, the Delphi method, and a multinomial logit model. The typology of coping and adaptation practices to climate change preferred by households and the reasons for those who failed to adapt are presented. Results revealed that improving technologies for increasing soil health was the most preferred adaptation practice, followed by planting early maturing and drought-tolerant food crop varieties, practicing water-saving irrigation methods or technologies, planting agroforestry systems, and finally perennial agriculture. In terms of coping mechanisms, engaging in off-farm activities was the most used, followed by collecting fuel wood for sale, selling assets like livestock, increasing water storage capacity, and changing farming structure. Small farm holdings, financial constraints, limited off-farm employment opportunities, inadequate infrastructure and technology, and a lack of information about adaptation practices were identified as the main barriers to undertaking adaptation. Performing the multinomial logit analysis, the variables that positively and significantly improve households' ability to adapt to climate change were identified and evaluated. The results of this study should help policymakers and climate change planners come up with better practices for the agricultural sector to adapt to the effects of climate change.